2004
DOI: 10.1128/jvi.78.17.9446-9457.2004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Interactions between Vaccinia Virus Complement Control Protein and Human Complement Proteins C3b and C4b

Abstract: The vaccinia virus complement control protein (VCP) is an immune evasion protein of vaccinia virus. Previously, VCP has been shown to bind and support inactivation of host complement proteins C3b and C4b and to protect the vaccinia virions from antibody-dependent complement-enhanced neutralization. However, the molecular mechanisms involved in the interaction of VCP with its target proteins C3b and C4b have not yet been elucidated. We have utilized surface plasmon resonance technology to study the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 56 publications
(84 reference statements)
0
51
0
Order By: Relevance
“…The binding abilities of SPICE, VCP, and the mutants to bovine C3b were determined using surface plasmon resonance (SPR)-based biosensor Biacore 2000 (Biacore, Uppsala, Sweden) (36). Bovine C3b (∼5000 response units, RU) labeled through its free thiol group with biotin (Supplemental Fig.…”
Section: Surface Plasmon Resonance Measurementsmentioning
confidence: 99%
“…The binding abilities of SPICE, VCP, and the mutants to bovine C3b were determined using surface plasmon resonance (SPR)-based biosensor Biacore 2000 (Biacore, Uppsala, Sweden) (36). Bovine C3b (∼5000 response units, RU) labeled through its free thiol group with biotin (Supplemental Fig.…”
Section: Surface Plasmon Resonance Measurementsmentioning
confidence: 99%
“…Sequence alignment of sCCPH with SPICE showed that sCCPH has Leu (Leu-106) and Arg (Arg-118) in the corresponding positions. Because earlier studies have shown that ionic interactions play a critical role in CCP-C3b/C4b interactions (34,(42)(43)(44) we suspected that Arg-118 might be responsible for the enhanced C3b cofactor activity. To further probe this possibility, we built a three-dimensional model of sCCPH by homology modeling using the crystal structure of VCP (45) as the template.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments were performed in phosphate-buffered saline-Tween (10 mM sodium phosphate, 145 mM NaCl, pH 7.4, containing 0.05% Tween 20) at 25°C. For proper orientation of these proteins, the free SH groups of both C3b and C4b were biotinylated and then immobilized on the streptavidin chip (Sensor Chip SA, Biacore AB) (34). FC-2 was immobilized with C3b (1592 RU), FC-3 was immobilized with C4b (1197 RUs), and FC-1 (blank flow cell) served as the control flow cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement C4b was immobilised on the NeutrAvidin-coated sensor surface in its physiological orientation by labelling its free exposed thiol group with biotin ( Figure 1A) [38]. The T M and T E response data for the C4b injection onto the NeutrAvidin layer occurred at 12 500 s (Figure 3).…”
Section: Dpi Analyses Of Immobilised C4bmentioning
confidence: 99%